Butyric acid production from recycled waste paper by immobilized Clostridium tyrobutyricum in a fibrous‐bed bioreactor. Issue 4 (16th April 2015) - Huang, Jin; Dai, Hongliang; Yan, Ren; Wang, Pu
Abstract: BACKGROUND: Recycled waste paper (RWP) has been considered as a low‐cost substrate for cost‐effective production of various biofuels and chemicals. The aim of this work was to utilize the fermentable sugar obtained from RWP, and thus to develop an alternative source of butyric acid to replace the petroleum‐based product. RESULTS: RWP hydrolysate was successfully utilized for enhanced production of butyric acid in a fibrous‐bed bioreactor (FBB) with a high titer (53.42 g L −1 ) and high selectivity (43.43 g g −1 butyrate/acetate ratio) in fed‐batch fermentation. A repeated‐batch fermentation process was carried out in which highly consistent butyrate yield (0.41 g g −1 utilized sugar), titer (20.96 g L −1 ), and productivity (1.62 g L −1  h −1 ) were achieved, demonstrating a stable and reliable long‐term performance. Glucose and xylose, two major fermentable sugars in RWP hydrolysate, could be simultaneously consumed for butyrate production, providing high substrate utilization efficiency. Moreover, the presence of a metabolic pathway shift from acetate‐forming pathway towards butyrate synthesis was confirmed. CONCLUSION: High concentration fermentable sugar solutions were obtained from recycled waste paper, and could be utilized successfully for butyric acid production. The results also showed that the process developed was cost‐effective and benign for environmental protection. © 2015 Society of Chemical Industry